Interspeech 2021 2021
DOI: 10.21437/interspeech.2021-1211
|View full text |Cite
|
Sign up to set email alerts
|

Presentation Matters: Evaluating Speaker Identification Tasks

Abstract: This paper details our evaluations and comparisons of speaker identification (SID) performance by listeners across different tasks. Experiment 1 participants completed traditional targetlineup (1-out-of-N speakers or out-of-set speaker) and binary (speaker verification) tasks. Experiment 2 participants completed trials online by using a clustering method by grouping speech recordings into speaker-specific clusters. Both studies employed similar speech recordings from the PTSVOX corpus. Our results showed parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…By instructing participants to sort 32 stimuli into 1 to 32 different speaker groups, Johnson et al suppressed the possibility of introducing artificial bias [21]. Recently O'Brien et al [44][45][46] developed a perceptual clustering method and reported unfamiliar listeners were effective at navigating the intuitive interface.…”
Section: Perceptual Speaker Identification Tasksmentioning
confidence: 99%
“…By instructing participants to sort 32 stimuli into 1 to 32 different speaker groups, Johnson et al suppressed the possibility of introducing artificial bias [21]. Recently O'Brien et al [44][45][46] developed a perceptual clustering method and reported unfamiliar listeners were effective at navigating the intuitive interface.…”
Section: Perceptual Speaker Identification Tasksmentioning
confidence: 99%